Psychological resilience and mood disorders: a systematic review and meta-analysis - Areeba Imran; Suleman Tariq; Flavio Kapczinski; Taiane de Azevedo Cardoso (Trends in Psychiatry and Psychotherapy, 2024)
Abstract Objective This systematic review aims to describe the relationship between psychological resilience and mood disorders. Methods This is a systematic review and meta-analysis. The following databases were searched on November 6, 2020: PubMed, PsycINFO, and Embase. Results Twenty-three articles were included and the majority of the studies included (95.7%) showed that psychological resilience has a positive impact in mood disorders. Our meta-analysis showed that individuals with bipolar disorder presented significantly lower levels of psychological resilience compared to controls (standardized mean difference [SDM]: -0.99 [95% confidence interval {95%CI}: -1.13 to -0.85], p < 0.001). In addition, individuals with depression had significantly lower levels of psychological resilience compared to controls (SDM: -0.71 [95%CI -0.81 to -0.61], p < 0.001). Conclusion Our results showed that individuals with mood disorders are less resilient than individuals without mood disorders. Our findings reinforce the importance of investigating interventions that may help to improve psychological resilience considering its positive impact in the context of mood disorders.